الدرس الصوتيّ في كليات رســائل النور لبديع الزمان سعيد النورسيّ - تومــــي, غنية (Revues faculté des lettres et des langues; No 14-15 (2014): مجلة كلية الآداب واللغات, 2014)
تحاول هذه الدراسة  تسليط الضوء على تناولات الداعية المفسّر التركيّ بديع الزمان النورسي للقضايا الصوتية من خلال تفسيره المعروف بكليات رسائل النور في إطار مقاربة لغوية تؤصّل لجملة مفاهيم تعكس التفكير اللغويّ للرجل لاسيما الصوتيّ منه؛ وذلك بالتعرّض لنظرته للصوت، و ربطه إيّاه بالإعجاز القرآنيّ، و التأكيد على وقوفه على كثير من المقولات الصوتية الحديثة   This study attempts to shed light on the issues of sound in the interpretation of the Turkish preacher Bediuzzaman Nursi known by Couliat rassael nour in part of an linguistic study to emphasizes the inter concepts reflect his linguistic thinking, particularly sound issue; by presenting his vision of the voice, and linking it to the sound miraculous of the holly Qur'an, and the emphasis on his big knowledge of many of the principles sound modern